Explorations in Austrian economics - Koppl, Roger, 1957- (Advances in Austrian economics, 2008)
Features papers presented at the inaugural Wirth Institute Conference on the Austrian School of Economics. This work explores issues in economic policy, applied economics, and pure theory from a variety of perspectives.